PROGRAM LEGISLASI DAERAH SEBAGAI PENGAWAL POLITIK HUKUM DI DAERAH - H.M. Soerya Respationo (Faculty of Law, Universitas Diponegoro, 2012)
ABSTRACT Since the passing of reforms in 1998 has brought changes to the constitutional system of centralized to decentralized Indonesia, it means a government authority handed over to autonomous regions, except for the central government affairs. The principle of autonomy emphasizes providing government authority to local governments to regulate and manage their own affairs within the unity state of framework. Follow-up of these reforms have also been carried out by the 1945 Amendment to change the power to make laws that are on the government initially submitted to parliament. National legal and political system was changed to affect the formation of the orientation and priorities of legislation, including legislation as part of program activities inherent in the process of formation of national law. Accordingly, any establishment of legislation to do with the deepening of the material, the synchronization and harmonization with other legislation, as well as open access and dissemination to increase community participation. One of the priorities that must be done within the framework of the development of national law is to harmonize legislation to establish a form of regulatory legal instruments that guarantee the implementation of the rule of law while providing the broadest possible benefits for thewelfare of the people, namely the Local Legislation Program. Keywords: Local Legislation, Legal Policy, Local Government. ABSTRAK Sejak bergulirnya reformasi tahun 1998 telah membawa perubahan pada sistem ketatanegaraan Indonesia dari sentralistik menjadi desentralistik, artinya sejumlah wewenang pemerintahan diserahkan kepada daerah otonom, kecuali urusan pemerintahan pusat. Prinsip otonomi daerah menekankan pada pemberian kewenangan pemerintahan kepada pemerintahan daerah untuk mengatur dan mengurus sendiri urusan pemerintahan yang menjadi kewenangannya dalam kerangka NKRI. Tindak lanjut dari reformasi ini juga telah dilakukan Perubahan UUD 1945 dengan merubah kekuasaan membentuk undang-undang yang pada mulanya berada pada Pemerintah diserahkan kepada DPR. Sistem dan politik hukum nasional pun berubah yang mempengaruhi orientasi dan prioritas pembentukan peraturan perundang-undangan termasuk kegiatan program legislasi sebagai bagian yang inheren dalam proses pembentukan hukum nasional. Sejalan dengan hal tersebut, maka setiap pembentukan peraturan perundang-undangan harus dilakukan dengan pendalaman materi, sinkronisasi dan harmonisasi dengan peraturan perundang-undangan lain, serta diseminasi untuk membuka akses dan meningkatkan partisipasi masyarakat. Salah satu prioritas yang harus dilakukan dalam rangka pembangunan hukum nasional adalah melakukan harmonisasi peraturan perundang-undangan dengan membentuk suatu instrumentasi hukum berupa peraturan yang lebih menjamin terlaksananya kepastian hukum sekaligus memberikan kemanfaatan yang seluas-luasnya bagi kesejahteraan rakyat, yaitu program legislasi daerah. Kata Kunci: Legislasi Daerah, Politik Hukum, Pemerintahan Daerah.